2013
DOI: 10.1111/bjh.12539
|View full text |Cite
|
Sign up to set email alerts
|

Targeted resequencing for analysis of clonal composition of recurrent gene mutations in chronic lymphocytic leukaemia

Abstract: SummaryRecurrent gene mutations contribute to the pathogenesis of chronic lymphocytic leukaemia (CLL). We developed a next-generation sequencing (NGS) platform to determine the genetic profile, intratumoural heterogeneity, and clonal structure of two independent CLL cohorts. TP53, SF3B1, and NOTCH1 were most frequently mutated (16Á3%, 16Á9%, 10Á7%). We found evidence for subclonal mutations in 67Á5% of CLL cases with mutations of cancer consensus genes. We observed selection of subclones and found initial evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 13 publications
5
33
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17] Now that main CLL genomic drivers have been uncovered by whole exome sequencing or whole genome sequencing studies and targeted NGS has been demonstrated as an accurate and reproducible technique in CLL, 30,31 it offers an affordable and more sensitive tool for mutational screening of patients with CLL in clinical practice. We focused on previously identified CLL drivers and used stringent quality filters and visual inspection to remove all possible false-positive calls.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Now that main CLL genomic drivers have been uncovered by whole exome sequencing or whole genome sequencing studies and targeted NGS has been demonstrated as an accurate and reproducible technique in CLL, 30,31 it offers an affordable and more sensitive tool for mutational screening of patients with CLL in clinical practice. We focused on previously identified CLL drivers and used stringent quality filters and visual inspection to remove all possible false-positive calls.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Although genomic studies have depicted the landscape of the clonal complexity of CLL, little is known about the clinical implications and dynamics of very small subclones that may be present, but are commonly undetected, in the leukemic cell population. [14][15][16][17] Understanding the significance of small CLL subclones might be particularly important if they are driven by genetic lesions associated with treatment resistance, such as TP53 mutations. In this respect, analysis of the subclonal architecture of TP53 mutations in the early disease phases may help anticipate the genetic composition of later phases of the disease, including chemorefractoriness and relapse, and may also predict the disease ultimate clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The application of ultra-deep-next generation sequencing (NGS) to track TP53 mutated subclones in CLL has provided a proof-of-concept that small tumor cell populations of very low clonal abundance can drive the overall disease course, and may represent informative and highly sensitive biomarkers of chemorefractoriness. 5 In addition to TP53, other cancer genes known to be recurrently mutated in CLL and significantly associated with poor survival include NOTCH1, SF3B1, and BIRC3.…”
mentioning
confidence: 99%